PENGAMBILAN KEPUTUSAN MEMPERTAHANKAN ATAU MENGHENTIKAN KEGIATAN USAHA “SO’YMAH Milk” DENGAN ANALISIS BIAYA RELEVAN - Antoro, Eko Wahyudi; Zuhroh, Nimatu; Astari, Ita Yoeli (Politeknik Negeri Sriwijaya, 2024)
In Jakarta, there is a handcrafted soy milk business called So'ymah Milk. In the third and fourth years of operation, So'ymah Milk has experienced a decline in sales. So'ymah Milk has contemplated stopping this company or keeping it going in light of this issue. With the decision-making paradigm of continuing the firm or shutting it down, studies of pertinent expenses are applied to aid in decision-making. The implementation of relevant cost analysis stems from its potential to compute future costs, facilitate present-day work performance comparison within the organization, and estimate future financial performance. Since all of the data for this study came from So'ymah Milk's financial records, a complete sample approach was employed. The information used to support the financial data analysis came from field observation findings and the compilation of financial reports. Based on the data analysis, So'ymah Milk made the decision to continue operating the firm since the financial data, observation results, and qualitative data demonstrated the numerous benefits of continuing operations over closing.